“Saraband” : o habitus sueco no filme de Ingmar Bergman - Barboza, Naylini Sobral (2015)
This research analyzes the construction process of the Swedish habitus that Ingmar Bergman seized and showed in his film work, particularly in the movie "Saraband" (2003). To perform this analysis, that is anchored in a ethnographic methodology, which i raise and analyze certain patterns of behavior, languages and beliefs of the Swedish people, to map the socio-cultural setting in which Bergman was immersed. Thus, my theoretical and methodological support, to the dialogue between the Swedish society and the filmmaker, through the film "Saraband", are the concepts of Norbert Elias (1993.1994, 1995, 1997, 2001, 2006, 2011): Configuration, individuation and habitus. The first two chapters are bibliographical and historical review of Bergman and about Sweden, then enter the third chapter, on the analysis of the film in the light of the information presented and procedural theory of Elias. In this analysis I could see how the interdependence between individual and society is reflected in the film.